ANALYZING MATHEMATICAL LITERACY ABILITIES IN TERMS OF COGNITIVE STYLE OF SIXTH GRADE STUDENTS: A CASE STUDY AT SD INPRES NIPA-NIPA - Nurul Wulan; Sukmawati Sukmawati; Baharullah Baharullah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This study aimed to describe the Mathematical literacy skills of Grade VI students of SD Inpres Nipa-Nipa, in terms of reflective and impulsive cognitive styles, based on the six levels of Mathematical literacy. This research was a descriptive study with a qualitative approach. The subjects of this study were two grade IV students, one student with a reflective style and another student with an impulsive style. The data collection began by giving a cognitive style test and an initial Mathematics test. Then, a Mathematical literacy test was also administered to determine the level of students’ literacy. After that, an interview was conducted to obtain more accurate data. The results showed that (1) the reflective student took a long time and was very circumspect in answering the Mathematical literacy test questions, so that the results were more accurate. The reflective student was able to answer the questions with clear procedures sequentially and was able to interpret and use representations based on information of the questions, so that it could take the right strategy to answer the question. These results revealed that the students were at the third level of mathematical literacy ability, (2) the impulsive student needed shorter time and was less careful in answering a Mathematical literacy test so that the results were less accurate. The results showed that the impulsive student could answer the question with an identified context and the relevant information with a clear question was available. In addition, the impulsive student could identify information obtained from the question and when he was given a stimulus. Thus, the impulsive student possessed the first-level of Mathematical literacy skills.